Securing Village Life Development in Late Colonial Papua New Guinea - MacWilliam, Scott (ANU Press, 2013)
Securing Village Life: Development in Late Colonial Papua New Guinea examines the significance for post-World War II Australian colonial policy of the modern idea of development. Australian officials emphasised the importance of bringing development for both the colony of Papua and the United Nations Trust Territory of New Guinea. The principal form that development took involved securing smallholders against the tendencies of other forms of capitalist development that might have separated households from land. In order to make household occupation of their holdings more secure and at higher standards of living, the colonial administration coordinated and supervised increases in production of crops and other agricultural produce. Contrary to suggestions that colonial policy and practice ignored indigenous agriculture and concentrated on plantation crops grown by international firms and expatriate owner-occupiers, the study shows how the main focus was instead upon increasing smallholder output for immediate consumption as well as for local and international markets. Simultaneously development stimulated increases in consumption, including of goods produced through manufacturing processes and imported into the colony. Only as Independence approached was the pre-eminence of the earlier focus upon smallholders weakened. In part the change occurred due to the political advance of the indigenous capitalist class and their allies seeking to extend their base in largeholding agriculture and related commercial activities. This advance and the uncertainty over which form of development would prevail once indigenes held state power in post-colonial Papua New Guinea stood in marked contrast to the definite direction pursued under the colonial administration of the 1950s and early 1960s.